YES : youth empowerment through sport (Caribbean Sport and Development Agency)
Focuses on developing authentic leadership experiences for youth in school and community settings as they move through an empowerment scale that progressively transfers control from adult leaders to youth sport leaders by increasing their leadership competencies and decision-making responsibilty through practice and mentorship.
Keywords: YOUTH